Self Efficacy Enhancement of Public School Teachers through Cognitive Behavior Therapy - Luaton, Toniruth; Vinluan, Lorelei (Yayasan Corolla Education Centre, 2023)
This study explores how Cognitive Behavior Therapy (CBT) can help improve the self-efficacy of elementary school teachers in public schools. It focuses on four questions: (1) What are the Self-efficacy levels and concerns of Public-School Elementary Teachers? (2) How do Public School Elementary Teachers address their Self-efficacy concerns? (3) How different are the Self-efficacy levels of Public-School Elementary Teacher before and after undergoing CBT? (4) What guidance/wellness program using CBT can be proposed for the enhancement of Self-efficacy of Public-School Elementary Teachers? A mixed method explanatory design was employed, and out of 101 teachers from five schools in San Jose del Monte Bulacan, five were chosen to participate in CBT sessions. Quantitative findings utilizing the New General Self-efficacy scale present that majority of the teachers demonstrate moderate to high levels of self-efficacy. Qualitative data indicated the self-efficacy concerns of teachers including computer skills, aging, health issues, motivation, task alignment and time management. To address these, they resort to mediocre work, talk directly to concerned persons, seek help from relatives, become careful about health, and most commonly, resort to sleeping. The CBT sessions markedly increased the posttest results and the teachers reported considerable positive changes in their thinking. This research promotes the understanding of the self-efficacy of teachers and offers valuable insights for upgrading the well-being and effectiveness of teachers. It also highlights the potential of Cognitive Behavior Therapy as an effective intervention for enhancing self-efficacy and showcases the importance of tailored wellness programs in building the holistic development of teachers.